Clinical Characteristics and Surgical Procedures for Children with Congenital Membranous Cataract - Jingji Long; Daoman Xiang; Zheng Guo; Lihong Chen; Feng Chen; Jianxun Wang; Wanhua Xie; Shiping He (Journal of Ophthalmology)
Objective. In a group case series, the clinical characteristics of congenital membranous cataract in children were studied to establish a system of classification and determine the surgical method suited for each type. Methods. Children (18 eyes) with congenital membranous cataract were examined by slit lamp, ultrasound biomicroscopy, and operating microscopy to classify cataracts. The clinical characteristics of congenital membranous cataract and its feature related to the surgical method were analyzed. Results. Five major types of congenital membranous cataracts were classified. All of the surgeries were successful. Anterior and posterior capsulorhexis was performed using Klöti RF capsulotomy tips. The capsular flap was removed, and anterior vitrectomy was performed using a vitrectomy cutter. Postoperative complications included posterior capsule opacification in 16.7% of the patients. Conclusion. Ultrasound biomicroscopy was used successfully to classify congenital membranous cataracts prior to surgery. Anterior and posterior capsulorhexis was performed using Klöti RF capsulotomy tips, and capsulectomy was performed using a vitrectomy cutter. These were effective techniques and should be considered for congenital membranous cataract removal surgery. This trial is registered with registration number chiCTR-OOC-17010913.